MODEL PEMBELAJARAN MENULIS BERBASIS KONTEKS DI SEKOLAH MENENGAH ATAS - Jusrin Efendi Pohan (Jurnal Education and Development, 2022)
This study aims to produce a valid, effective, and practical context-based review writing model that can be use. The development of this model is motivated by a crucial problem where students are still low in writing reviews. This is due to less productive teaching materials and teachers tend to convey material at the rote level, not yet touching on synthetic thinking. As a result, students become bored and uncomfortable in learning to write reviews practically. This type of research is research and development using the ADDIE model is Analysis, Design, Development, Implementation, and Evaluation. This context-based review writing model was developed through stages starting from the prototype stage, expert validation, to evaluation. Testing of this model was carried out on grade XI students of General High School 7 Padang Bolak. Data collection was carried out using questionnaires, observations, and in-depth interviews. The data obtained is done by analyzing descriptively. The findings of this study are a valid, practical, and effective context-based review writing model that can increase students' motivation in learning to write reviews.